The Effectiveness of Self-Help Groups for Adolescent Substance Misuse: A Systematic Review. Issue 3 (3rd May 2016) - Bekkering, Geertruida E.; Mariën, Dorien; Parylo, Oksana; Hannes, Karin
ABSTRACT: A review of the effectiveness and potential harms of self-help groups in substance-misusing adolescents was performed. Twelve studies were examined. All studies were case series with important methodological shortcomings. The findings of these studies were summarized using a narrative synthesis approach. Results indicated that self-help group attendance appears to reduce alcohol and drug use, including abstinence. However, the lack of methodological rigor in these studies precludes definitive conclusions.